Assessing the Impact of Technological Innovations in Healthcare: A Bibliometric Study of Medical Devices - Muhammad Azhar Irwansyah; Supriyandi; Tera Lesma; Muhammad Umer Farooq Mujahid; Adi Nugroho Susanto Putro (Westscience Press, 2023)
Technological innovation in healthcare has emerged as a transformative force, reshaping the landscape of medical practices and patient care. This research conducts a comprehensive bibliometric analysis to assess the impact of technological innovation in healthcare. Using VOSviewer, co-authorship, citation, and keyword co-occurrence networks are visualized and analyzed. A systematic literature review is conducted to collect relevant articles within a specific timeframe. The analysis identifies key research areas, influential authors, and the overall impact of healthcare technology. The findings provide valuable insights for policymakers, researchers, and practitioners, guiding evidence-based decision-making and shaping the future of healthcare technology.